Students individual work on pediatric surgery chair as one of credit-modular education system factors - Lyaturinska, O. V.; Makarova, M. O. (Zaporozhye Medical Journal, 2014)
Introduction. Joining European educational space for Ukrainian medical higher education is a complex and multifaceted task that requires addressing many issues at the state level and in each university. Modern medical society more than anyone else needs professionals who are able to think creatively and independently. Newest technologies require young professionals in addition to getting education also acquire such qualities as self-reliance, confidence, responsibility, the ability to live and work in the new environment, be socially oriented. Therefore, individual work of future doctors is of great importance. Individual work is a means of students' learning activation and obligatory condition for the self-sufficiency formation in the following work. To be able to think independently is the most important professional quality that characterizes the ability of a future doctor to systematize, plan and make decisions on which health and sometimes the patient's life depend.[1, 3, 4, 5]. Object. The object of the educational process is the education of a competent person, future-oriented, able to solve common problems and tasks on the basis of acquired learning experiences and adequate assessment of the clinical situation. The lecturer should bring to a student’s mind knowledge and skills dependence from his motivation and personal contribution to the learning process, handling the thesis "no one can be taught, but everyone can learn". Students should have the skills of individual work, firm aspiration for continuous replenishment, renewal and knowledge improvement in the process of individual work. During individual work student must learn to distinguish cognitive task, to choose means of its resolving, to exercise self-control operations for literacy performance of tasks, to improve methods of the creative knowledge realization. Skills and knowledge formation of students’ individual work can occur not only at the conscious, but on an intuitive basis as well. Individual work management realizes on the basis of clear planning of individual work and regular monitoring of its results. Lecturers should be aware that individual work task should be clearly formulated with the volume of work and the requirements for its accomplishment indication. Terms of the assignment completion should be clearly stated. Students should know the stages and form of task verification. For this methodical guidelines for task implementation should be stated in the task. Conclusions. 1. The need for self-education depends on the educational level of student’s consciousness and the greatest interest in the problems of self-improvement show students who have a high level of educational identity. 2. Education of the need in constant self-education is a part of measures to improve the efficiency and quality of medical professionals. 3. It is necessary to take into account students’ individual characteristics during the tasks given for individual work on problematic topics of the course, working out the necessary methodological materials for students’ individual work organization and its administration by the lecturer.